2013
DOI: 10.17269/cjph.104.3770
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Tobacco Use Co-morbidities in Canada

Abstract: OBJECTIVES: Tobacco use co-morbidities, including co-occurring tobacco use, substance use and mental health problems, are a serious public health issue that has implications for treatment and policy. However, not enough is known about the prevalence of various types of tobacco use co-morbidities among the Canadian population. The purpose of this study was to increase understanding of the extent of this issue through an examination of prevalence and correlates of tobacco use co-morbidities in Canada.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 24 publications
2
8
0
1
Order By: Relevance
“…18 COMPASS also utilizes purposive sampling for recruitment of participating schools from different geographical locations-Ontario, Alberta, British Columbia, Quebec and Nunavut. 10 While the sampling approach may have impacted external validity, many of the findings presented here are comparable with other large-scale studies on alcohol use and binge drinking prevalence among Canadian youth, namely the Canadian Community Health Survey and the Canadian Alcohol and Drug Use Monitoring Survey (42% prevalence of alcohol use), 11 and the Canadian Student Tobacco, Alcohol and Drugs Survey (44% prevalence of alcohol use and 24% prevalence of high-risk drinking). 13…”
Section: Strengths and Limitationssupporting
confidence: 78%
See 2 more Smart Citations
“…18 COMPASS also utilizes purposive sampling for recruitment of participating schools from different geographical locations-Ontario, Alberta, British Columbia, Quebec and Nunavut. 10 While the sampling approach may have impacted external validity, many of the findings presented here are comparable with other large-scale studies on alcohol use and binge drinking prevalence among Canadian youth, namely the Canadian Community Health Survey and the Canadian Alcohol and Drug Use Monitoring Survey (42% prevalence of alcohol use), 11 and the Canadian Student Tobacco, Alcohol and Drugs Survey (44% prevalence of alcohol use and 24% prevalence of high-risk drinking). 13…”
Section: Strengths and Limitationssupporting
confidence: 78%
“…Data from the Canadian Alcohol and Drug Use Monitoring Survey (CADUMS) and the Canadian Community Health Survey (CCHS) showed significantly higher prevalence of binge drinking and problem drinking (based on the AUDIT scale) in current smokers versus non-smokers. 11,12 Using data from CADUMS and CCHS, Kirst and colleagues reported that the magnitude of association between current smoking and binge drinking was larger for adolescents aged between 12 and 17 years compared to those aged 18 years and older. 11 The difference in this association for the two age groups is striking and indicates a need for interventions among youth who use multiple substances.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A score of eight or greater on the AUDIT is indicative of hazardous alcohol use. The use of a cut-off score of 8+ as a positive screen for both males and females has been used in Ontario and Canadian national surveys [ 23 , 24 ].…”
Section: Methodsmentioning
confidence: 99%
“…[1][2][3][4][5][6] Controlled substances are drugs that have been identified by the Canadian federal government as having an elevated potential for abuse or addiction, and are listed in schedules I to V of Canada's 1996 Controlled Drugs and Substances Act. 7 Abuse of controlled medication refers to the consumption of substances intended for medical treatment for the purpose of producing euphoric feelings of well-being (a "high"), whereas misuse refers to a deviation from prescribed instructions, such as taking an additional sleeping pill when the first did not have the desired effect.…”
mentioning
confidence: 99%